Thermal and physiochemical properties of pellets with power aims made of sawmill residual product - Casanova, Pedro (2017)
Sawmill residual product of Pylon (Hyeronima alchorneoides) and Eucalyptus (Eucalyptus spp) species was used to produce pellets under different conditions of densification. Experimental equipment was used to determine the thermal conductivity, thermal diffusivity and specific heat. Physicochemical properties of the pellets obtained under different conditions of densification, such as ash content and calorific value were determined. The content of nitrogen, chlorine and sulfur present in the material used to produce the pellets was estimated. Thermal conductivity values were determined between 0,253 W/mK and 0,279 W/mK; 1,748 m2/s and 2,314 m2/s for the thermal diffusivity, and in the case of specific heat values between 3,019 kJ/kgK and 2,183kJ/kgK were determined. The high heat values was between 18 907 kJ/kg and 18 960 kJ/kg, an ash content of 1,31 % on a dry basis was determined. Finally, it was determined that the content of nitrogen, chlorine and sulfur present in the residual biomass used, corresponds to 0,1129 %, 0,0592 % and 0,0317 %, respectively. A direct relationship between increasing the bulk density of the pellets and the thermal properties was determined. The calorific value and ash content were not significantly affected by the treatments applied. The estimated content of N, Cl and S corresponds to that expected in the selected biomass. Comparison of the properties of the pellets produced under the conditions studied -densification, against regulations-, showed acceptable results, entering these in terms of different categories of quality.